2009
DOI: 10.4049/jimmunol.0802948
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Pathological and Clinical Nephritis in Systemic Lupus Erythematosus-Prone New Zealand Mixed 2328 Mice Doubly Deficient in TNF Receptor 1 and TNF Receptor 2 via a Th17-Associated Pathway

Abstract: TNF-␣ has both proinflammatory and immunoregulatory functions. Whereas a protective role for TNF administration in systemic lupus erythematosus (SLE)-prone (New Zealand Black ؋ New Zealand White)F 1 mice has been established, it remains uncertain whether this effect segregates at the individual TNFR. We generated SLE-prone New Zealand Mixed 2328 mice genetically deficient in TNFR1, in TNFR2, or in both receptors. Doubly-deficient mice developed accelerated pathological and clinical nephritis with elevated leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 66 publications
2
85
1
Order By: Relevance
“…The induction of SLE following TNF blockade reported in this study is further highlighted by the recent results of Jacob, et al 23 in the lupus-prone NZM 2328 mouse model, which show that abrogating the effects of TNF by deleting both TNF receptors leads to a heightened and distinct inflammatory pathway that accelerates onset of disease, supporting the notion that anti-TNF may be contraindicated in the treatment of SLE.…”
Section: Rheumatologysupporting
confidence: 60%
“…The induction of SLE following TNF blockade reported in this study is further highlighted by the recent results of Jacob, et al 23 in the lupus-prone NZM 2328 mouse model, which show that abrogating the effects of TNF by deleting both TNF receptors leads to a heightened and distinct inflammatory pathway that accelerates onset of disease, supporting the notion that anti-TNF may be contraindicated in the treatment of SLE.…”
Section: Rheumatologysupporting
confidence: 60%
“…A number of studies have indicated that Th17 is involved in the pathogenesis of a variety of inflammatory diseases, including rheumatoid arthritis, asthma, inflammatory bowel diseases [38][39][40], and lupus nephritis [41,42]. Further studies should be performed to identify the effects of anti-P on the production of IL-17 in PBMC from healthy donors.…”
Section: Discussionmentioning
confidence: 96%
“…Expression of Stat3, which is also driven by oxidative stress [24], is increased in both lupus T [25] and B cells [13]. Stat3-dependent signals play a key role in the differentiation of Th17 cells [26], which appear to mediate nephritis in patients with SLE [27,28]. …”
Section: T Cell Dsyfunction In-systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%